Revision of the Ulopinae leafhoppers (Hemiptera: Cicadellidae) of the Indian subcontinent, I. Ulopini genera: Daimachus, Radhades and Ulopsina - Viraktamath, C.a.; Webb, M. D. (Zootaxa, 2019)
The Ulopinae leafhopper genera of the tribe Ulopini from the Indian subcontinent (Daimachus Distant and Radhades Distant) are redescribed. Four new species of Daimachus are described: D. matheranensis sp. nov. (India: Maharashtra), D. robustus sp. nov. (India: Kerala), D. sirsiensis sp. nov. (India: Karnataka) and D. sudindicus sp. nov. (India: Karnataka, Kerala). Ulopa brunnea Pruthi 1930 is treated as a junior synonym of Daimachus exemplificatus Distant 1916 based on a study of the male genitalia of both species. The latter species, together with Radhades crassus Distant and Ulopsina Dai, Viraktamath & Zhang are redescribed and a new subgenus of Ulopsina, Indoulopa subgen. nov. is described from Sub-Himalayan region with Ulopsina (Indoulopa) himalayana sp. nov. as the type species; the genus is reported for the first time from the subcontinent. Key to genera and species dealt with are also provided, all taxa are illustrated and lectotypes are designated for Daimachus exemplificatus, Ulopa brunnea and Radhades crassus.